2005
DOI: 10.1158/1078-0432.ccr-04-1549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Synthetic Retinoid Fenretinide on Circulating Free Prostate-Specific Antigen, Insulin-Like Growth Factor-I, and Insulin-Like Growth Factor Binding Protein-3 Levels in Men with Superficial Bladder Cancer

Abstract: Purpose: Fenretinide (4-HPR) is a synthetic retinoid that has shown a preventive activity in prostate cancer animal models.Experimental Design: We measured the changes in total and free prostate-specific antigen (PSA) and its association with insulin-like growth factor I (IGF-I) and IGFBP-3 levels after 1 year of treatment in 24 subjects given 4-HPR and 24 control subjects enrolled in a randomized bladder cancer prevention trial.Results: No significant effect of 4-HPR was observed on total and free fraction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Several studies have associated serum haptoglobin concentration with many cancers, including ovarian cancer, breast cancer, small cell lung cancer, esophageal squamous cell carcinoma, pancreatic cancer, liver cancer and prostate cancer (Ahmed et al, 2004;Awadallah et al, 2004;An et al, 2005;Ang et al, 2006;Okuyama et al, 2006;Fujimura et al, 2008;Shah et al, 2010). Furthermore, Dunzendorfer et al (1980) found increased serum haptoglobin levels in patients with urogenital tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have associated serum haptoglobin concentration with many cancers, including ovarian cancer, breast cancer, small cell lung cancer, esophageal squamous cell carcinoma, pancreatic cancer, liver cancer and prostate cancer (Ahmed et al, 2004;Awadallah et al, 2004;An et al, 2005;Ang et al, 2006;Okuyama et al, 2006;Fujimura et al, 2008;Shah et al, 2010). Furthermore, Dunzendorfer et al (1980) found increased serum haptoglobin levels in patients with urogenital tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the development of cancer involves a series of changes in protein expression in the serum and cancerous tissues (Serrano et al, 2005;Gkialas et al, 2008;Varela et al, 2008;Hyrsl et al, 2009;Kim et al, 2011). However, the only way to monitor disease progression is to analyze bladder specimens.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy between the aforementioned animal and human data may be related to an insufficient dose of 4HPR used in the human studies. Extrapolations from recent in vitro studies indicate that a daily 4HPR dose of 200 mg (considered a “safe” dose for many of the previous cancer chemoprevention and therapy trials [38]) likely does not achieve apoptogenic concentrations of the drug in most target tissues in vivo ; perhaps with the exception of tissues with a high fat content such as breast tissue. It is believed that 4HPR concentrations ≥5 μM are needed at target tissues to achieve an apoptogenic response in transformed cells [2, 4].…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that 4HPR concentrations ≥5 μM are needed at target tissues to achieve an apoptogenic response in transformed cells [2, 4]. This concentration is about five-fold higher than the peak plasma level typically attained with a 200 mg daily dose of 4HPR [38], which would suggest that we are way off the mark for potentially obtaining a consistent anticancer effect for this agent in humans.…”
Section: Resultsmentioning
confidence: 99%